A Modular Synthesis of Conformationally Preorganised Extended β‐Strand Peptidomimetics. Issue 42 (17th August 2015) - Yamashita, Tohru; Knipe, Peter C.; Busschaert, Nathalie; Thompson, Sam; Hamilton, Andrew D.
Abstract A promising strategy for mediating protein–protein interactions is the use of non‐peptidic mimics of secondary structural protein elements, such as the α‐helix. Recent work has expanded the scope of this approach by providing proof‐of‐principle scaffolds that are conformationally biased to mimic the projection of side‐chains from one face of another common secondary structural element—the β‐strand. Herein, we present a synthetic route that has key advantages over previous work: monomers bearing an amino acid side‐chain were pre‐formed before rapid assembly to peptidomimetics through a modular, iterative strategy. The resultant oligomers of alternating pyridyl and six‐membered cyclic ureas accurately reproduce a recognition domain of several amino acid residues of a β‐strand, demonstrated herein by mimicry of the i, i+2, i+4 and i+6 residues.